Heterosexual Parents’ Decisions and Experiences of Disclosure to Their Donor-Conceived Children in the Last Ten Years: A Mixed Methods Systematic Review - Duff, Michelle (Auckland University of Technology, 2022)
Disclosure of donor conception has been advocated in several jurisdictions in recent years, especially in those that practice or mandate identity-release donation. This systematic review aims to integrate knowledge from research over the past ten years concerning heterosexual parents’ decisions to disclose donor conception to their children, and their experiences of disclosure, in both jurisdictions which allow anonymous donation (non- mandated jurisdictions) and those which require donation to be identity-release (mandated jurisdictions). This may provide a context for understanding the disclosure patterns of heterosexual parents in Aotearoa New Zealand and the effects on their well-being, as the first donor-conceived children born under the provisions of the Human Assisted Reproductive Technology [HART] Act (2004) turn 18 in late 2022. Methods A bibliographic search of English language, peer-reviewed, and published journal articles from six computerized databases was undertaken from January 2012 to August 2022. A Preferred Reporting Items for Systematic reviews and Meta-Analyses [PRISMA] 2020 approach was used. Results Twenty-six reports met the inclusion criteria, representing 23 study populations and the decisions of 2,114 participants. The review shows that parental disclosure decisions and experiences may be understood via a biopsychosocial framework, and are impacted by multiple interacting intrapersonal, interpersonal, and external contextual and social factors across both mandated and non-mandated jurisdictions. There appears to be a general trend towards early disclosure with most of the parents in the studies included in this review disclosing to their donor-conceived children before the age of ten. Additionally, there appears to be a trend towards increased disclosure over time, specifically in mandated identity-release jurisdictions. The varied methodological approaches and sample sizes across the reports making it difficult to integrate the findings are discussed. Conclusion Intrapersonal, interpersonal, and external factors influence parents’ decisions and experiences around the disclosure process. The need for further research across many aspects of the donor conception field has been demonstrated by this review, including the role of mandating identity-release, gender, culture, donor type, and professional psychological support in parental disclosure decisions and experiences.
Keywords: gamete donation; sperm donation; oocyte/egg donation; embryo donation; parental disclosure; identity-release; anonymous donor; mixed methods; systematic review